Myth as a form of knowing in Algirdas Julius Greimas’ semiotics - Meržvinskaitė, Birutė (Literatūra, 2019)
The article focuses on the peculiarities of the creation, representation and persuasion of scientific abstract and mythical figurative knowing in A. J. Greimas’ reconstruction of Lithuanian mythology. Mythical knowing is understood in two ways: as a cultural construct, a part of cultural knowledge that is limited to the existential and discoursive experience of the reader, and as a special ability or skill of the mythical gods. In order to explain the similarities and differences between mythical and scientific knowing, the concepts of narrativity and believing are used. Narrative structures imply the fundamental patterns of thinking about man and the world (existence/action, death/life, nature/culture) and convert individual understanding into a collective one. The emphasis on the rational and rhetorical point in the concept of believing partially reduces the contradiction between the strict methodological reason of the semiotical tradition and the practical and cunning reason of an mythical textual tradition.